Substituting sugar confectionery with fruit and healthy snacks at checkout - a win-win strategy for consumers and food stores? a study on consumer attitudes and sales effects of a healthy supermarket intervention - Lise L. Winkler; Ulla Christensen; Charlotte Glümer; Paul Bloch; Bent E. Mikkelsen; Brian Wansink; Ulla Toft (BMC, 2016)
Abstract Background The widespread use of in-store marketing strategies to induce unhealthy impulsive purchases has implications for shopping experience, food choice and possibly adverse health outcomes. The aim of this study was to examine consumer attitudes and evaluate sales effects of a healthy checkout supermarket intervention. The study was part of Project Sundhed & Lokalsamfund (Project SoL); a Danish participatory community-based health promotion intervention. Methods Consumer attitudes towards unhealthy snack exposure in supermarkets were examined in a qualitative pre-intervention study (29 short in-store interviews, 11 semi-structured interviews and three focus group interviews). Findings were presented to food retailers and informed the decision to test a healthy checkout intervention. Sugar confectionery at one checkout counter was substituted with fruit and healthy snacking items in four stores for 4 weeks. The intervention was evaluated by 48 short exit interviews on consumer perceptions of the intervention and by linear mixed model analyses of supermarket sales data from the intervention area and a matched control area. Results The qualitative pre-intervention study identified consumer concern and annoyance with placement and promotion of unhealthy snacks in local stores. Store managers were willing to respond to local consumer concern and a healthy checkout intervention was therefore implemented. Exit interviews found positive attitudes towards the intervention, while intervention awareness was modest. Most participants believed that the intervention could help other consumers make healthier choices, while fewer expected to be influenced by the intervention themselves. Statistical analyses suggested an intervention effect on sales of carrot snack packs when compared with sales before the intervention in Bornholm control stores (P < 0.05). No significant intervention effect on sales of other intervention items or sugar confectionery was found. Conclusions The present study finds that the healthy checkout intervention was positively evaluated by consumers and provided a 'responsible' branding opportunity for supermarkets, thus representing a win-win strategy for store managers and consumers in the short term. However, the intervention was too modest to draw conclusions on long-term sales and health implications of this initiative. More research is needed to assess whether retailer-researcher collaborations on health promotion can be a winning strategy for public health.